The only one who knows : a novel - Matlin, Lisa (Bantam, 2026)
"With her polished persona as a morning show co-host, Minnow Greenwood seems to have it all. But behind the camera, something's about to break. When a public meltdown shatters her facade, Minnow flees back to Kangaroo Bay--a grimy fishing town on Australia's southern coast, where locals vanish and something deadly hunts in the water. On her first night back, a horrifying shark attack rocks the town, adding another body to the unsettling list of deaths and disappearances. Then a former colleague arrives to investigate, so she reluctantly teams up with him to find answers for herself and keep her own dark secrets buried. But with danger closing in, Minnow must unearth her town's deadly past and face the darkness festering inside her before she becomes the next to disappear."